Risk of tramadol induces seizure following naloxone therapy: Systematic review and meta-analysis: Tramadol induces seizure following naloxone therapy - Shadnia, Shahin; Rahimi, Mitra; Mostafazadeh, Babak; Erfan Talab Evini, Peyman; Meshkini, Mohammad; Simani, Leila; Mahdavinejad, Arezou; Sedaghatmonfared, Helia; Razeghi, Ehsan; Daneshmand, Mahsa; et al. (Iranian Journal of Pharmaceutical Sciences, 2025)
Tramadol overdose is a significant global health issue with a rising prevalence. Several studies have highlighted a notable occurrence of seizures in individuals experiencing tramadol overdose. The incidence of seizures following the administration of naloxone in patients with tramadol overdose remains a topic of debate. This systematic review and meta-analysis assessed the incidence of tramadol-induced seizures after the administration of naloxone in individuals who had overdosed on tramadol. Our study conducted a comprehensive search across multiple medical databases to identify articles reporting tramadol-induced seizures following naloxone therapy. The search encompassed Cochrane Central Register of Controlled Trials, MEDLINE-PubMed, Scopus, Ovid, Embase, Springer, Web of Sciences, Science Direct, and PubMed, with all searches completed by November 30, 2023. Additionally, the search encompassed reference lists of included studies and gray literature sources such as dissertations, organizational publications, and websites to gather supplementary data. The analysis involved calculating pooled odds ratio for seizure incidence between groups based on subgroups related to tramadol abuse history, seizure history, and intubation needs using fixed-effect models and odds ratios for gender distribution using random-effect models, all with 95% confidence intervals (CI). The results indicate a marginally elevated seizure risk in the naloxone group versus controls; however, this difference did not reach statistical significance (OR: 0.91, 95% CI: 0.63–1.31; p=0.62). Subgroup analyses based on previous seizure history and tramadol abuse revealed slight differences between the naloxone and control groups in these subgroups, leading to an overall odds ratio of 0.89, 95% CI: 0.64, 1.23, with a P-value of 0.48. Further subgroup analysis indicated no significant disparity between the two groups concerning the need for intubation (p=0.13) and male gender distribution (p=0.49). In conclusion, the study suggests that the use of naloxone in patients with tramadol toxicity does not independently trigger seizures. Naloxone administration was not associated with an increased risk of intubation or seizures. However, the lack of randomized clinical trials in this area necessitates more robust investigations to draw definitive conclusions.